PENINGKATAN HASIL BELAJAR SISWA KELAS IV MELALUI METODE TUTOR SEBAYA PADA MATA PELAJARAN BAHASA INDONESIA SDN 165732 KOTA TEBING TINGGI - Sri Susilowati (Universitas Negeri Medan, 2019)
The purpose of this study was to find out the learning outcomes of Indonesian Language class IV SD Negeri 165732 Tebing Tinggi City. The type of research conducted is classroom action research. The action given is implementation through the Peer Tutor Method. As the subjects in this study were Grade IV students of SD Negeri 165732 in Tebing Tinggi City, amounting to 36 people consisting of 15 male students and 21 female students. This research is planned to be held in the first semester of the 2018/2019 academic year. The results of observational cycle 1 and cycle 2 experienced an increase in cycle 1, the number of active students 55.60% rose to 90.60% in cycle 2, the process skills in cycle 1 were 50.00% up to 88.90 in cycle 2, the number students who complete from 27.22% to 94.44% in cycle 2, the average value in cycle 1 is: 58.33 up to 73.90 in cycle 2. Keywords: Learning outcomes, peer tutors, Indonesian